The Effort of Build Tolerance Society with Cross-Faith Dialogue in Lumajang Regency - Soffi, Dewi Ariyanti; Haque, Arina (Fakultas Ushuluddin Adab dan Dakwah IAIN Metro-Lampung, 2023)
The multi-religious reality cannot be avoided by the people of Indonesia, one of which is in the Lumajang Regency. If not treated properly, this condition will create the potential that leads to religious conflict. FKUB (Forum for Religious Harmony) is a bridge between religion and the state in uniting a pluralistic Indonesian society to create religious spaces. Interfaith dialogue is a meeting place for community and religious leaders through joint discussion sessions to open people's insights regarding differences through qualitative research methods with an ethnographic approach. Then for data collection techniques, the authors conducted observations, interviews, and literature studies both online and offline. The theoretical analysis carried out in this case study uses the concept of